Algal Synthesis of Selenium Nanoparticles: A Green Approach to Biomedical Solutions - Payal Chaurasia,; Khushaboo Soni,; Preeti Maurya,; Sanjay Singh, (The Bioscan, 2025)
The green synthesis of selenium nanoparticles with algae is a sustainable and eco-friendly method. Algae have highly active compounds that serve as natural reducing agents by which inorganic selenium converts into selenium nanoparticles This process takes place via metabolic pathways, both intracellular and extracellular, that allow selenium ions to be reduced into stable nanoscale particles. UV-Vis spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and dynamic light scattering (DLS) are used to characterize the size, shape, crystalline structure, and surface properties of algae-derived SeNPs. These SeNPs show impressive antioxidant, antibacterial, and anticancer properties, thus showing potential as candidates for many biological applications such as drug delivery, wound healing, and cancer therapy. In addition, their biocompatibility and biodegradability reduce the threat of toxicity, thus making them more amenable to therapeutic applications than chemically synthesized nanoparticles. The paper discusses the advantages of algae use for the synthesis of SeNPs, indicates procedures of characterization as well as possible biological usage of SeNPs and further expands on the troubles of the scaling up green synthesis procedure and the future need for further research toward the improvement of their application at the clinic level, resulting in an overall view of additional possibilities for medicine.